The vital role of animal, marine, and microbial natural products against COVID-19 - Aljawharah A. Alqathama; Rizwan Ahmad; Ruba B. Alsaedi; Raghad A. Alghamdi; Ekram H. Abkar; Rola H. Alrehaly; Ashraf N. Abdalla (Taylor & Francis Group, 2022)
Context Since the outbreak of SARS-CoV-2, researchers have been working on finding ways to prevent viral entry and pathogenesis. Drug development from naturally-sourced pharmacological constituents may be a fruitful approach to COVID-19 therapy.Objective Most of the published literature has focussed on medicinal plants, while less attention has been given to biodiverse sources such as animal, marine, and microbial products. This review focuses on highlighting natural products and their derivatives that have been evaluated for antiviral, anti-inflammatory, and immunomodulatory properties.Methods We searched electronic databases such as PubMed, Scopus, Science Direct and Springer Link to gather raw data from publications up to March 2021, using terms such as 'natural products', marine, micro-organism, and animal, COVID-19. We extracted a number of documented clinical trials of products that were tested in silico, in vitro, and in vivo which paid specific attention to chemical profiles and mechanisms of action.Results Various classes of flavonoids, 2 polyphenols, peptides and tannins were found, which exhibit inhibitory properties against viral and host proteins, including 3CLpro, PLpro, S, hACE2, and NF-κB, many of which are in different phases of clinical trials.Discussion and conclusions The synergistic effects of logical combinations with different mechanisms of action emphasizes their value in COVID19 management, such as iota carrageenan nasal spray, ermectin oral drops, omega-3 supplementation, and a quadruple treatment of zinc, quercetin, bromelain, and vitamin C. Though in vivo efficacy of these compounds has yet to be established, these bioproducts are potentially useful in counteracting the effects of SARS-CoV-2.